(untitled) (Global Journal of Human-Social Science, 2023)
Brazil has the world s largest system of protected areas and its largest concentration of conservation units is found in the Amazon biome On the other hand even with a significant amount of protected spaces this conservation system is not able to contain or suppress the environmental damage that affects the ecosystems of these areas Hence the need to seek a methodology capable of providing effectiveness to the protected areas through criminal analyzes that cover damage and destruction legal norms and environmental regulation in other words the green criminology theory This paper aimed to falsificate the preventive parameters based on green criminology pointed out by Flores Konrad and Flores 2017b in order to refute corroborate or expand them applying them to the Amazon Conservation Units located in Rond nia and under state and local administrative competence For this investigation the hypothetical-deductive method was used Results fostered corroboration of the preventive parameters pointing out the need for their applicability toward effectiveness in the preservation of the analyzed protected spaces The data we collected serve as a reflective warning regarding concerns for conservation units as their implementation is not enough to consolidate their main objective to preserve the natural capital of these areas